Comprehensive abattoir checklist / Rafeah Saidon … [et al.] - Saidon, Rafeah; Ishak, Amal Hayati; Ruzulan, Zulaipa; Jaafar, Nurzahidah; Syed Abdullah, Sharifah Fadylawaty (Division of Research and Industry Linkages, 2017)
Abattoir checklist is needed to facilitate auditing process in slaughterhouse. Appropriate slaughtering in Islam involves multiple elements to be fulfilled including selection of animal, selection of slaughter man, certified slaughterhouse, hygienic requirements, slaughtering utensils, location and most important all the halal requirements are observed completely. Therefore, a proper checklist is required as to ensure no element is left out. Unfortunately, there is no comprehensive and standard form of checklist currently used by the authorised auditor at local and international levels. The purpose of this innovation is to introduce a comprehensive abattoir checklist that completely meets all the requirements. This checklist is beneficial specifically to auditors in assisting their auditing process as well as to the consumers at large in assuring the meat that is accessible to them is halalan tayyibban.